PENGENALAN LITERASI MEDIA REALIA HERBARIUM DAN TERARIUM BERBASIS KERAGAMAN TUMBUHAN HUTAN TROPIS PADA GURU KELAS AWAL DI SDN 016 TARAKAN - Fadhlan Muchlas Abrori; Aidil Adhani; Fitri Wijarini; Darius Rupa; Agustina Dai Pain (Biopedagogia, 2021)
Abstract: The teaching and learning process in school needs to emphasize the contextual aspect to know the relation between material and life around. One of the media that can be used is herbarium and terrarium. This program provides understanding and training of herbarium and terrarium-making techniques to teachers to be used in the learning process in the classroom, especially in the early classes. This program's result includes: the average of plant identification skill's teacher before the program was 34.5 and after implementation of the program was 85.4. Based on the result of the ability of teacher of making herbarium, the highest score on the aspect of "active involvement in the activity" with an average was 86.5, while the lowest score on the aspect of "making conclusion according to result" with an average was 79, 5. The highest result of the average herbarium product is the completeness of the plant organ, and the completeness of the herbarium with an average value was 100. The lowest value is on the layout of the herbarium, with an average value was 84. In the terrarium making, the results obtained very well, the highest yield on the aspect of the planting media composition, the container's suitability, and the life span of the plant with a value was 100. Keywords : Herbarium, Terrarium, Media